Lung involvement in children with COVID‐19 multisystem inflammatory syndrome. Issue 2 (28th November 2022) - Ghezzi, Michele; Longoni, Emma; Munari, Alice; Raso, Irene; Biganzoli, Giacomo; Zuccotti, Gianvincenzo; D'Auria, Enza
Abstract: Since the beginning of the COVID‐19 pandemic, multisystem inflammatory syndrome in children (MIS‐C) has been reported in increasing numbers, mostly focusing on cardiac dysfunction. Very few studies have evaluated lung involvement in terms of imaging findings, while data regarding pulmonary function in children with MIS‐C are not available. The purpose of our study was to evaluate lung involvement in MIS‐C by imaging and lung function by structured light plethysmography (SLP) at hospital admission and 6 months afterwards. Spirometry is the gold standard technique to evaluate lung function in children. However, SLP has the advantage of not requiring contact with the patient, offering an effective solution for the evaluation of lung function during the pandemic. To our knowledge this is the first study that aims to investigate pulmonary function by SLP in children with MIS‐C.